Economical effect of rainfall toward production and cost of production / Muhammad Fathi Mohamed Yudin and Nur Amalina Ismail - Mohamed Yudin, Muhammad Fathi; Ismail, Nur Amalina (Faculty of Plantation and Agrotechnology, 2018)
The role of rainfall in plant could not be overemphasized because rainfall determines the amount of moisture present in the soil which is ultimately made available to plants. The objective of this study is to identified the effect of the rainfall toward production and cost. The research is done by using monthly data from 2015 until 2017 that get from Syarikat Ladang Sungai Terah, Ladang Subong Gua Musang. This study test whether there have long run relationship between the variable. The Augmented Dickey Fuller (ADF) show that the series are significant at first difference. There also have a co-integrating relationship in this model. The vector error correction model (VECM) were conducted in this test. Result show that the positive significant that increasing of the rainfall will increase the production. For the impulse respons showed that there is significant relationship between cost and maintenance and rainfall. As a conclusion we can conclude that there has many factor that effect the production. Rainfall -was not directly give the impact to the production because it depends on the environment